Hubungan Antara Panjang Lengan dan Daya Ledak Otot Lengan Dengan Kemampuan Kids Atletik Lempar Turbo Pada Siswa Kelas 4, 5, 6 SDN Gendro II Kecamatan Tutur Kabupaten Pasuruan - Ahkam, Muhammad Masalus Sairil; Nurrochmah , Siti (Universitas Hamzanwadi, 2025)
This study seeks to determine and examine the relationship between arm length and arm muscle explosive power simultaneously with turbo throwing ability in 4th, 5th, and 6th grade students. The method used is descriptive quantitative with an explanatory approach. The population in this study were male students in grades 4, 5, 6 SDN with a total of 50 students. The sampling technique used purposive proportional systematic sampling technique with a portion of 95% of 44 students in grades 4, 5, 6 totaling 42 students. The research instrument used in this research uses a form of physical condition test, namely arm muscle explosiveness and Kids athletic ability test turbo throwing. The data collection technique uses measurement techniques in the form of tests including measurements of arm length, arm muscle explosiveness, and the ability of Kids turbo throwing athletics. The results of the analysis technique use parametric inferential statistics in the form of multiple correlation of two predictors as independent variables. The results of the multiple correlation test obtained a coefficient = 0.503 and Sig. p = 0.000 < α = 0.05. The conclusion of this study is that there is a positive and linear relationship between arm length and arm muscle explosiveness simultaneously with turbo throwing ability.